Evaluation of Softening of Clayey Soil Stabilized with Sewage Sludge Ash and Lime - Kamyar Norouzian; Nader Abbasi; Jahangir Abedi Koupai (Civil Engineering Journal, 2018)
Production of sewage sludge have raised increasing concerns due to negative environmental effect. Sewage Sludge Ash (SSA) is used as a new type of additive for clay. Laboratory tests were performed on clay samples to study the mechanism of sewage sludge ash (SSA) and Hydrated Lime (HL) soil stabilization. Different SSA contents (0, 5, 10, 15%) and hydrated lime (0, 1, 3 and 5%) were added to the soil samples. 288 samples were prepared, and unconfined compressive strength tests were carried out. The samples were tested under optimum water content and also saturated conditions with three replications. The results of the coefficient of softening indicated that by adding SSA and hydrated lime to clay soil simultaneously, the stabilized clay soils can be applied in the moist and saturated condition. According to the results, the samples of SSA contents 0% with hydrated lime 5% and SSA contents 10% with hydrated lime 5% can be placed in the vicinity of moisture.